Boom : marketing to the ultimate power consumer--the baby boomer woman - Brown, Mary, 1959- (American Management Association, 2006)
"Women make the vast majority of purchasing decisions in the United States, spending trillions of dollars every year on everything from food and clothing to appliances, cars, vacations, real estate, and much more. One huge, affluent segment of that demographic wields more spending clout than any other: Baby-Boomer women. Born between 1946 and 1964, these women represent a portion of the buying public no marketer can afford to ignore. With successful careers, investments made during the "boom" years, and inheritances from parents or husbands, they are more financially empowered than any previous generation of women. But what is it that will make these women spend their money on your products? Meet Mary Brown and Carol Orsborn, whose exclusive business it is to find out what makes Baby-Boomer women tick -- and buy. With BOOM, they reveal the results of proprietary research that has helped their firm's five-star clients outclass the competition by reaching and resonating with this powerhouse demographic. BOOM brings together the insights of dozens of market leaders in a wide array of industries, insiders who have learned (sometimes the hard way) what works and what doesn't in the battle for the hearts and minds of the "ultimate power consumer." You will learn: How to increase your market share of today's most lucrative consumer demographic What your competition and other industry leaders are doing to reach Baby- Boomer women How to minimize the risks and maximize the potential of your efforts in this market How to find, interpret, and present information and statistics and build a strong business case to your colleagues, shareholders, company executives, and others Intelligence for making savvy decisions and communicating the clear message that your target customer wants to hear You'll also get the authors' exclusive Imago Diagnostic (ID) tool for identifying exactly what resonates with Boomer women, along with the Seven Things You Don't Know About Baby-Boomer Women (But Should). At the age when they are more financially comfortable than ever, Baby-Boomer women are now poised and energized to drive consumer markets to unbelievable new highs. With the eye-opening information and cutting-edge strategies in BOOM, your company will be set to enjoy an amazing ride to the top."--Publisher's website